Enhanced Age-Related Resistance to Tomato Yellow Leaf Curl Virus in Tomato Is Associated With Higher Basal Resistance - Zhang, Jing-Ru; Liu, Shu-Sheng; Pan, Li-Long (Frontiers in Plant Science, 2021)
Tomato yellow leaf curl virus (TYLCV) is one of the most notorious plant pathogens affecting the production of tomato worldwide. While the occurrence of age-related resistance (ARR) against TYLCV has been reported, the factors impacting its development remain unknown. We conducted a series of experiments with three tomato cultivars that vary in basal resistance to TYLCV to explore factors involved in the development of ARR. Our data indicate that ARR is more pronounced in tomato cultivars with higher basal resistance. Additionally, increased plant biomass in older plants does not contribute to ARR. Virus source plants with a younger age at initial inoculation facilitates virus acquisition by whiteflies. Finally, an analysis on plant hormones suggests that salicylic acid (SA) may play a major role in the development of ARR in tomato against TYLCV. These findings provide new insights into the developmental resistance in tomato against TYLCV as well as clues for the deployment of ARR in the management of diseases caused by TYLCV.